-7(x+5)+3(x-6)=

Simple and best practice solution for -7(x+5)+3(x-6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(x+5)+3(x-6)= equation:


-7(x+5)+3(x-6)=0

We simplify the equation to the form, which is simple to understand
-7(x+5)+3(x-6)=0

Reorder the terms in parentheses
+(-7x-35)+3*(x-6)=0

Remove unnecessary parentheses
-7x-35+3+*(+x-6+)=0

Reorder the terms in parentheses
-7x-35+(+3x-18)=0

Remove unnecessary parentheses
-7x-35+3x-18=0

We move all terms containing x to the left and all other terms to the right.
-7x+3x=0+35+18

We simplify left and right side of the equation.
-4x=+53

We divide both sides of the equation by -4 to get x.
x=-13.25

See similar equations:

| f-1(2)= | | 5-(8-x)=3-(x-6) | | -(v-2)=-4(v-8)-8v | | x(x+3)=-8 | | (2x^2)+5x+8=0 | | 16z=-128 | | 7-q-q-2q=80 | | 4p-25=-32+5p | | 4p-12=-3+p | | -7x-10x=-85 | | 4x-10x=70 | | -5x-15=-95 | | -60=3+9x | | (3x^2)-5x-7=0 | | (2x^2)+8x=0 | | 1+x^2=0 | | (2x^2)-7x-1=0 | | 27a^3x^4-8x=0 | | 8+2x=x+40 | | 3y+24+6-2=33 | | -28+4=0 | | ln(x+1)ln(x)+ln(x^2)=1 | | ln(x+a)ln(x)+ln(x^2)=1 | | 53-2x=5x | | 11x-10=54 | | 6p^2+25-119=0 | | (6a^3+6a^2-7)+(5a^3-6a+8)= | | 2x^2-45=0 | | y+24y+144= | | 8a+12b+4= | | 9x+12y+15= | | 6a-18b+12c= |

Equations solver categories